IMPLEMENTASI TAFAKUR DALAM PROSES BIMBINGAN DAN KONSELING SEBAGAI UPAYA MENINGKATKAN KESADARAN DIRI [IMPLEMENTATION OF TAFAKUR IN THE GUIDANCE AND COUNSELING PROCESS AS AN EFFORT TO ENHANCE SELF-AWARENESS] - Agung, Ririh; Nurjannah, N (Acta Islamica Counsenesia: Counselling Research and Applications, 2023)
This research aims to explain the implementation of tafakur in the guidance and counseling process as an effort to enhance self-awareness. The research method used is library research, which involves collecting data from various library research such as books, articles, journals, and related studies. The findings of the study indicate that the implementation of tafakur in the guidance and counseling process has significant potential in improving clients' self-awareness. By applying tafakur, clients can gain a deeper understanding of themselves, recognize and manage emotions better, and enhance the quality of their relationships with themselves and others. The implications of this research emphasize the need to expand the understanding and utilization of tafakur in the practice of guidance and counseling. Counselors should have good access to current literature and integrate this knowledge to assist clients in enhancing their self-awareness. The application of tafakur in guidance and counseling can be an effective means to help clients achieve personal development.